A Comprehensive Flood Risk Analysis in Senior High Schools - Ristiani, Trifia Safira; Wibowo, Yunus Aris; Dewi, Ratih Puspita (Universitas Muhammadiyah Surakarta, 2025)
Flood disasters are a serious threat to various regions in Indonesia, one of which is Klaten Regency. On February 15, 2023, flooding occurred in Klaten Regency after being hit by heavy rain for 2 days which caused rivers to overflow and embankments to break, entering villages and also several schools, one of which is SMKN 1 Rota Bayat. At this time the flood problem is clearly visible, therefore it is necessary to analyze the level of danger, vulnerability, and risk of flood disasters in Klaten Regency to reduce the risk of flood disasters, especially in school environments. Flood disaster analysis was carried out by utilizing InaRISK data which was then processed and applied using Geographic Information Systems (GIS) through software in the form of ArcGIS. The research method is quantitative research with a survey research design. The results of this study indicate (1) The level of flood danger in Klaten Regency shows that the highest flood danger is found in 5 schools in the south and east, while in the north and west there are 67 schools that are relatively safe from the threat of flooding. (2) There are 39 Senior High Schools and equivalent in Klaten Regency that have a high level of social vulnerability to flood hazards. There are 53 schools with a low level of physical vulnerability to flood hazards. Based on this, it shows that Senior High Schools and equivalent in Klaten Regency are in the high or medium category of vulnerability to flood hazards. (3) The risk of flood disasters in Klaten Regency is categorized into the medium-low class, namely there are 67 schools. It is hoped that this research can determine the level of flood disaster risk in Senior High Schools in Klaten Regency.